Identifying Partisan Gerrymandering and Its Consequences: Evidence from the 1990 US Census Redistricting - Navid Sabet; Noam Yuchtman (Center for Economic Studies and ifo Institute (CESifo), 2023)
We empirically identify politically-motivated redistricting and its consequences, studying the effects of changed electorate composition on US congressional district boundaries and on political outcomes. We exploit the 1986 Immigration Reform and Control Act (IRCA), which legalized millions of immigrants, changing local electorates without changing demographics — legalized immigrants were already counted in the census. Where Democrats controlled the 1990 redistricting process, higher IRCA populations were associated with more spatially distorted districts. Consistent with theory, Democrats packed Hispanics (their ardent supporters) into majority-minority districts. House delegations had more Hispanics suggesting that partisan gerrymandering, in this case, served the historically disadvantaged.
Keywords: D70; P00; J10; 330; gerrymandering; minority political representation; immigrant legalization; state governance